2011
DOI: 10.4319/lo.2011.56.6.2176
|View full text |Cite
|
Sign up to set email alerts
|

Enduring physiological and reproductive benefits of enhanced flow for a stony coral

Abstract: We experimentally examined the in situ, long-term effects of flow on the coral Pocillopora verrucosa over a 2-yr period. Eighteen coral nubbins were positioned on stages protected from the ambient flow with transparent walls. Six of the corals were exposed to ''enhanced flow'' with underwater pumps (15-20 cm s 21 ), while another other six were grown under ''reduced-flow'' conditions (, 1 cm s 21 ), and a further six nubbins were set up as a control treatment exposed to ambient natural flow conditions on stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 74 publications
0
26
0
Order By: Relevance
“…2, A1) may explain why P. inflata has been observed in some surveys, only to be absent after 1-3 years in subsequent surveys (Glynn 1999). In addition, a few studies that have monitored the morphology of Pocillopora corals for 9-24 months have reported similar changes in swollen branches (Nakamura and Yamasaki 2006;Mass et al 2011;see below). Our findings show that some coral colonies can maintain their morphology over long periods (unchanged colonies over more than 3 years, fig.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…2, A1) may explain why P. inflata has been observed in some surveys, only to be absent after 1-3 years in subsequent surveys (Glynn 1999). In addition, a few studies that have monitored the morphology of Pocillopora corals for 9-24 months have reported similar changes in swollen branches (Nakamura and Yamasaki 2006;Mass et al 2011;see below). Our findings show that some coral colonies can maintain their morphology over long periods (unchanged colonies over more than 3 years, fig.…”
Section: Discussionmentioning
confidence: 84%
“…For example, transplanted fragments of P. damicornis began to develop thicker, more swollen branches after 9 months of constant high (20 cm/s) flow (Nakamura and Yamasaki 2006). Pocillopora verrucosa also developed short but swollen branches after 2 years in higher flow (Mass et al 2011). Models also predict that thicker, swollen branches will be induced by high water flow and light availability (Filatov et al 2010;Chindapol et al 2013).…”
Section: Discussionmentioning
confidence: 86%
“…Calcification occurs extracellular but under strictly controlled conditions (e.g. Mass et al, 2011) beneath the calicoblastic tissue, isolated from seawater by two layers of tissue and the coelenteron. Since the skeleton cores come from living colonies it would be incorrect to refer to the samples as 'fossils'; instead we refer to them as 'naturally aged' to distinguish them from the experimentally heated samples.…”
Section: Massive Porites Coral Core Samplesmentioning
confidence: 99%
“…(B) A coral that was grown in an in situ controlled flume setup with “reduced flow” condition (∼1 cm s −1 ) (C–E) Corals were grown in the in-situ controlled flumes setup with “enhanced flow” condition (15–20 cm s −1 ) [32]. Arrows indicate flow direction.…”
Section: Introductionmentioning
confidence: 99%